2005
DOI: 10.1144/1470-9236/04-012
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide pollution of the Triassic Sandstone aquifer of South Yorkshire

Abstract: Diffuse pollutants such as pesticides pose a significant threat to groundwater quality. Following the wet autumn and winter of 2000-2001 an upturn in trace pesticide concentrations was detected in blended water drawn from part of the Triassic Sandstone aquifer. A groundwater sampling and monitoring programme was undertaken to assess whether this increase would continue. Over a period of 18 months, 190 groundwater samples were collected from the upper part of the aquifer and analysed for 40 pesticides and for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…As pointed out by Morvan et al (2006), few studies have tried to estimate the trend of groundwater contamination after a pesticide has been banned. In a study focusing on a sandstone aquifer by Gooddy et al (2005), pesticides sampled in groundwater over a period of 18 months did not show any trend. In a countrywide case study focusing on atrazine and its metabolite desethylatrazine presented for Germany by Tappe et al (2002), persistence in groundwater was common occurrence.…”
Section: Introductionmentioning
confidence: 91%
“…As pointed out by Morvan et al (2006), few studies have tried to estimate the trend of groundwater contamination after a pesticide has been banned. In a study focusing on a sandstone aquifer by Gooddy et al (2005), pesticides sampled in groundwater over a period of 18 months did not show any trend. In a countrywide case study focusing on atrazine and its metabolite desethylatrazine presented for Germany by Tappe et al (2002), persistence in groundwater was common occurrence.…”
Section: Introductionmentioning
confidence: 91%
“…Recently the occurrence of both pesticides and their metabolites within groundwater have been identified (Kolpin et al, 1996(Kolpin et al, , 2004Gooddy et al, 2002Gooddy et al, , 2005Johnson et al, 2001;Postle et al, 2004). Pesticides in groundwater have been found to originate from arable land (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of mixed farming and smallholdings with potential mixed and multiple diffuse and point sources of pesticide pollution is also common in lowland areas of sandstone outcrop. Together these factors mean that the experience here is also likely to be representative of pesticide pollution problems at many sites, and even thorough surveys of the catchment may not be able to identify the sources or pathways (Gooddy et al 2005). Despite the implementation of a complex, yet highly flexible ground water modeling tool, this work demonstrated that the source of the pesticide problem could not be identified or controlled.…”
Section: Discussionmentioning
confidence: 99%